Books Fit for a King:The Presentation Copies of Martin Bucer's De regno Christi (London, British Library, Royal MS. 8 B. VII) and Johannes Sturm's De periodis (Cambridge, Trinity College, II.12.21 and London, British Library, C.24.e.5). (2015) - Pohl, Benjamin; Tether, Leah
No abstract available